PENGARUH KEPEMIMPINAN ISLAMI, BUDAYA ORGANISASI ISLAM, DAN KEPUASAN KERJA TERHADAP KINERJA PERAWAT (Studi pada Rumah Sakit PKU ‘Aisyiyah Kabupaten Boyolali) - Salma, Hana Farida; Mas’ud, Fuad (Diponegoro Journal of Management, 2023)
ABSTRACT Nurses are part of the health workforce and their quantity dominates in terms of human resources in hospitals. The performance of nurses needs to be considered because nurses are the most closely related and directly related to patients as the main object of hospital operations. PKU ‘Aisyiyah Hospital in Boyolali Regency, as one of the major hospitals that seeks to provide excellent health facilities for patients, is inseparable from the performance role of nurses. Superior nurse performance also has an impact on improving hospital performance and the best professional service to patients. This study aims to determine the effect of islamic leadership, islamic organizational culture, and job satisfaction on the performance of nurses at PKU 'Aisyiyah Hospital in Boyolali Regency. Collecting research data through a questionnaire with as many as 96 respondents and the census method. Testing and data analysis used is multiple linear using Statistical Package for Social Science (SPSS) version 25 with a likert scale measurement technique of 1-7. The results showed that the variables of islamic leadership, islamic organizational culture, and job satisfaction had a positive and significant effect on the performance of nurses at PKU 'Aisyiyah Hospital in Boyolali Regency both partially and simultaneously with a coefficient of determination of 64,7%